2018
DOI: 10.1111/anu.12679
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nucleotide-rich yeast supplementation improves growth, innate immunity and intestinal morphology of Pacific white shrimp (Litopenaeus vannamei)

Abstract: An 8‐week feeding trial was conducted to evaluate the effects of dietary nucleotide (NT)‐rich yeast supplementation on growth, innate immunity and intestinal morphology in Pacific white shrimp (Litopenaeus vannamei). Four isonitrogenous and isolipidic practical diets were formulated to contain 0 (control), 10, 30 and 50 g/kg of NT‐rich yeast, respectively. A total of 480 shrimp with an average initial body weight of 1.86 ± 0.02 g were randomly allocated into four groups, with four replicates per group and 30 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 50 publications
5
36
0
Order By: Relevance
“…Furthermore, supplementation of the diet containing 1% squid visceral paste with the palatability enhancer gave similar results as 3% squid visceral paste. This increase in intestinal fold height will likely result in an enhanced area for nutrient absorption and has been reported previously in white shrimp associated with the dietary supplementation with nucleotides and yeast extracts (Guo et al, 2016;Xiong et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, supplementation of the diet containing 1% squid visceral paste with the palatability enhancer gave similar results as 3% squid visceral paste. This increase in intestinal fold height will likely result in an enhanced area for nutrient absorption and has been reported previously in white shrimp associated with the dietary supplementation with nucleotides and yeast extracts (Guo et al, 2016;Xiong et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…For instance, Xiong et al. (2018) reported that the dietary supplement of 10 and 30 g/kg YE presented similar final body weight (FBW), specific growth rate (SGR) and FCR with the shrimp control diet. Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, better growth performance and feed utilization in shrimp fed D + G could be linked to the larger absorption area in the intestine. Although there is limited information on the effects of either individual or combinations of nucleotides on shrimp intestinal conditions, there is a great deal of similarity of this study with the other investigations on whiteleg shrimp where commercial nucleotide products such as nucleotide‐rich yeast (Xiong et al., 2018) and commercial nucleotides Rovimax (Guo et al., 2016). Xiong et al.…”
Section: Discussionmentioning
confidence: 65%
“…Xiong et al. (2018) were reported to have significantly improved the gut condition with greater sizes of intestinal folds contributing to the gut functions. Guo et al.…”
Section: Discussionmentioning
confidence: 99%